2007
DOI: 10.1152/ajplung.00459.2005
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in zinc homeostasis underlie endothelial cell death induced by oxidative stress from acute exposure to hydrogen peroxide

Abstract: Oxidative stress has been associated with multiple pathologies and disease states, including those involving the cardiovascular system. Previously, we showed that pulmonary artery endothelial cells (PAECs) undergo apoptosis after acute exposure to H(2)O(2). However, the underlying mechanisms regulating this process remain unclear. Because of the prevalence of H(2)O(2) in normal physiological processes and apparent loss of regulation in disease states, the purpose of this study was to develop a more complete un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
62
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(64 citation statements)
references
References 60 publications
(61 reference statements)
2
62
0
Order By: Relevance
“…Taken together, these observations are consistent with a model that oxidative processes release zinc from MT by redox regulation (29). Although the mechanism which accounts for the increase in cytoplasmic zinc is still elusive, the available data suggest that zinc release occurs via a ROS-mediated pathway (11,40,41,43). Thus, ROS induced by UVB radiation may attribute to UV-induced rising zinc in HEKa through oxidative stress.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Taken together, these observations are consistent with a model that oxidative processes release zinc from MT by redox regulation (29). Although the mechanism which accounts for the increase in cytoplasmic zinc is still elusive, the available data suggest that zinc release occurs via a ROS-mediated pathway (11,40,41,43). Thus, ROS induced by UVB radiation may attribute to UV-induced rising zinc in HEKa through oxidative stress.…”
Section: Discussionsupporting
confidence: 87%
“…Though the exact mechanism behind UV-induced toxicity is yet to be elucidated, many studies have suggested oxidative stress playing an important role in UVB elicited DNA damage, cell membrane disruption and subsequent cell death (11)(12)(13)(24)(25)(26). Several lines of evidence indicate that oxidative and nitrosative stress lead to an increase of intracellular zinc and zinc cytotoxicity that may, in turn, stimulate and interfere with signaling pathways (8)(9)(10)40,41). Zinc is normally tightly regulated inasmuch as intracellular concentrations of free zinc have been estimated to be in the pico-or nanomolar concentration range (2,5,6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitochondrial membrane potential was analyzed using the lipophilic cation 5,5¢6,6¢-tetrachloro-1,1¢,3,3¢-tetraethyl benzimidazolyl carbocyanine iodide as previously described (11,57).…”
Section: Analysis Of Mitochondrial Membrane Potentialmentioning
confidence: 99%
“…Some of these differences in interpretation are likely to be due to the fact that apoptosis and necrosis are not "either/or" alternative death mechanisms, but appear to be the opposite ends of a spectrum of cell death pathways (12). For example, lactate dehydrogenase release has been used to identify necrosis by some researchers, but apoptosis by another (13), whereas unengulfed apoptotic cells may also release lactate dehydrogenase following secondary necrosis (14), suggesting this marker may not efficiently discriminate between the two pathways. Similarly, release of HMGB1 has also been reported to occur during both necrosis and apoptosis (15).…”
mentioning
confidence: 99%